Landscape As Cultural Identity In Cau Bau Kan Movie - Teddy Hendiawan; Aris Rahmansyah (Balong International Journal of Design, 2019)
The aim of this research is to investigate the landscape as forming identity in the Cau Bau Kan movie scene. However, the landscape depicted is often symbolic, and often contributes to social formation, impacting on human associations and social norms. The purpose of this study is to know the meaning of landscape into a cultural identity from the Cau Bau Kan movie. This study uses texture analysis to reveal surface quality in a film. The use of textural analysis to interpret and analyze the interrelations of narrative, style, and meaning of the strategy of applying aspects of landscape as cultural identity.